Glaucoma surgery - Akil, Handan; Anastasopoulos, Eleftherios; Aquino, Maria Cecilia; Aref, Ahmad A.; Assia, Ehud I.; Bettin, Paolo; Khaw, Peng Tee (Basel : Karger, 2017)
The first edition of this volume, published in 2012, has become an indispensable reference for clinicians, a fact that inspired the making of this 2nd edition. The book starts with a discussion of current achievements and limitations of the medical therapy of glaucoma. The focus is then placed on conventional glaucoma procedures such as trabeculectomy, deep sclerectomy, and glaucoma drainage device surgery. A chapter is dedicated to the postoperative management of filtering procedures. Further chapters review the role of the ocular surface and the issue of modulation of the scarring processes in glaucoma surgery. The second section covers some promising new devices and techniques. The final part addresses the surgical approaches to some specific clinical challenges: angle-closure glaucoma, concomitant cataract and glaucoma, pediatric glaucoma, and refractory glaucomas. This volume provides residents and general ophthalmologists with valuable new insights into the fascinating and sometimes complex aspects of glaucoma surgery. It will also assist glaucoma specialists when they review and validate therapeutic approaches with their patients.
La función de los autores fue determinada por el catalogador
Keywords: GLAUCOMA -- CIRUGÍA; GLAUCOMA -- TRATAMIENTO